Analisis Hukum Pidana terhadap Tindak Pidana Perjudian Online bagi Anak - Ina Nur Jannah; Ismail Marzuki (CV Rewang Rencang, 2025)
This research analyzes online gambling crimes involving children and their legal implications. The growing presence of online gambling poses risks to children's mental, social, and economic aspects. A normative juridical approach is used by analyzing related regulations, such as Law No. 1 of 2024 on Information and Electronic Transactions and Law No. 35 of 2014 on Child Protection. The findings indicate that online gambling is subject to criminal sanctions, with the crucial role of parents, the government, and society in prevention. Recommendations are also made to tighten supervision and enhance legal understanding among children and teenagers.